Interlanguage Pragmatics of Suggestion by Indonesian Efl Learners - Rizky, Hanif Safika, Agus Wijayanto, Ph.D, Mauly Halwat Hikmat, Ph.D (2016)
This study is a pragmatic study on Indonesian EFL learners in different semesters to express giving suggestion strategies. This study was conducted to analyze suggestion strategies and politeness strategies used by Indonesian EFL learners by using qualitative approach. Subjects of this study are the first semester and third semester by Indonesian EFL learners. Data for this study is taken from learners through the Discourse Completion Task (DCT) which consisted of nine situations with different familiarities and social status. Learners in each semester are asked to write the expression of giving suggestion to complete the DCT. Their responses are collected to be analyzed based on the suggestion strategies by Guerra and Martinetz and also to be analyzed based on the politeness strategies by Brown and Levinson. The findings of the study show that the most frequently used category of suggestion by Indonesian EFL learners was Direct Suggestion (DS) in the forms of performative verb and in the imperative, and Conventionalized Forms Suggestion (CFS) forms of possibility, should, conditional, recommend, and interrogative. The findings also show that familiarities did not have significant influence on Indonesian EFL learners when they chose suggestion strategies. The other finding shows that the most frequently used category of politeness strategies by Indonesian EFL learners was Bald On-Record (BOR). Key words: interlanguage pragmatic, suggestion strategies, politeness strategies